EFFECT OF CHICORY (CICHORIUM INTYBUS L.) LEAVES EXTRACT TO PROTECT CERTAIN LIVER ENZYMES IN MICE AGAINST CARBON TETRACHLORIDE-INDUCED HEPATOTOXICITY - Saddam, A. C. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Chicory contains dietary inulin and oligofructose compounds which have a beneficial effect on metabolism, as well as polyphenol type derivatives, which may be responsible for the antioxidant properties. The effect of different concentrations of the hydroalcoholic extract of dried powdered leaves of chicory on CCl4-induced hepatotoxicity in vivo in mice, has been studied. Thirty-five mice (20-30 g) of age four weeks were randomly divided into 5 groups (seven in each). The mice orally received three different concentrations of chicory leaves extract (CLE) before injection for 3 consecutive days by CCl4. The study showed that CCl4 caused elevation in serum GOT, GPT, and ALP activities in mice, but there was no pronounced elevation in total protein and albumin. Pretreatment of mice with 75, 150, and 300 mg/kg/bwt of CLE protected the liver against CCl4-induced cytotoxicity. CLE significantly (p